Lessons learnt from a scientific peer-review training programme designed to support research capacity and professional development in a global community - Ella August; Tamrat Endale; Julie M Buser; Kirby L Morris; Veronica Millicent Dzomeku; Yolanda R Smith (BMJ Global Health)
High-quality peer-reviewer training open to researchers across the globe has the potential to improve the published literature, however, this type of training is not widely available. In this paper, we describe an online peer-reviewer training programme, highlight its effectiveness in building peer review and writing skills, and discuss challenges and lessons learnt. This training programme, open to researchers across the globe, acquaints participants with challenges to and inequities in publishing and educates them about writing effective peer reviews. A focal point is how to provide specific and respectful feedback to help authors get accepted for peer review at an academic journal. Forty-nine participants from or residing in six continents completed the training. All programme evaluation respondents agreed that the orientation helped them gain a better understanding of their role as a peer reviewer at Pre-Publication Support Service. Most agreed that the training was helpful in improving their peer-review skills, and that the training was helpful in improving their writing skills. Participants wanted more networking and collaboration opportunities with other peer reviewers, inclusion of a qualitatively researched example paper and improved communication about the required time commitment. Our online programme with multiple time options was geographically inclusive but internet connectivity was challenging for some participants. Peer-reviewer training programmes can help researchers build their peer review and writing skills and enhance participants’ understanding of disparities in publishing. Integrating a geographically diverse group of researchers has the potential to enrich the discussions and learning in such a programme.